P11.64.A Long-term follow up and translational data from the ReoGlio phase Ib trial of GM-CSF and intravenous pelareorep (Reovirus) alongside standard of care in GBM. (5th September 2022) - Short, S; Kendall, J; West, E; Chalmers, A; McBain, C; Melcher, A; Collinson, F; Phillip, R; Brown, S; Samson, A
Abstract: BACKGROUND: We previously reported safety data from a phase Ib, open-label study of intravenous oncolytic virus pelareorep with GM-CSF alongside standard chemoradiotherapy in newly diagnosed glioblastoma confirming that the combination is well tolerated. We now report on long-term follow up and analysis of translational samples from tumour and blood in a subset of patients. METHODS: 15 patients with newly diagnosed GBM were treated with GM-CSF 50μg subcutaneously on days 1-3 and intravenous pelareorep on days 4-5 in weeks 1 and 4 of chemoradiotherapy, and subsequently in week 1 of each adjuvant temozolomide course: 7 patients received 1x10 10 TCID50 (dose level 1); 8 received 3x10 10 TCID50 (dose level 2). The primary objective was to determine the maximum tolerated dose of pelareorep and GM-CSF with standard chemoradiotherapy. Following a protocol amendment we also collected survival data in all patients up to August 2021. Serial blood samples were taken from three patients, at baseline, during chemoradiotherapy and in the first adjuvant cycle. Peripheral blood mononuclear cells were analysed for immune checkpoint expression by flow cytometry, RNAseq gene expression and T-cell receptor clonality, whilst plasma cytokines were quantified by Luminex. RESULTS: This combination was well tolerated with 87% of patients completing treatment as planned. Survival data analysis showed that median OS was 12.6 months in dose level 1 and 16.1 months in dose level 2, median OS for all patients was 13.1 months. The 24-month survival estimate for all patients was 25.0%, 16.7% for dose level 1 and 33.3% for dose level 2. One patient in dose level 1 remains alive at 43 months post registration without further treatment. Laboratory data showed that pelareorep infusion resulted in inflammatory cytokine and chemokine secretion, immune checkpoint modulation, and upregulation of inflammatory pathways. There was also increased peripheral clonal tumour-specific T-cell proliferation following pelareorep infusion. CONCLUSION: Although based on small numbers, these long-term follow up data suggest this may be an active combination in a subset of GBM patients. Translational data confirm that pelareorep potentially activates tumour-targeting immune pathways in GBM, with consequential immune checkpoint modulation. These data support a combination clinical trial of pelareorep, radiotherapy and immune checkpoint blockade in GBM.